The role of stressful coping styles in depression and anxiety levels on parents of children with autism spectrum disorder (Annals of Medical Research, 2021)
Aim: The purpose of this research is the determination of depression and anxiety levels and their impact on the style of coping with stress of parents of children with Autism Spectrum Disorder (ASD).Material and Methods: Research was conducted with parents of 73 children with ASD, who come to the rehabilitation center. Personal Information Form, Stress Coping Styles Scale, Beck Depression Inventory and State and Trait Anxiety Scale were used to the relational screening method.Results: It was found that the mean state and trait anxiety scores of parents was high and parents chose one of the self-confidence confidence approach to cope with stress.The self-confident approach alone reduced the despair negatively by -49.9%, but the submissive approach did not affect variables. Conclusion: It was found that the despair of the family members decreased when they preferred the self-confident coping approach.
Keywords: Autism spectrum disorder; coping styles; depression; anxiety; stress; comorbidity